Writing, Printing and Wrapping Papers from Mixtures of Hardwoods from Maharashtra State - Guha, S. R. D.; Mathur, G. M.; Sharma, Y. K.; Dhoundiyal, S. N.; Lad, J. B.; Desai, S. C. (Indian Forester, 1970)
The paper gives the results of the work done on mixture of hardwoods of three different regions, Chanda, Ballarshah and North Dhulia of Maharashtra State. The results show that the chemical pulps can be made from these mixtures for writing, printing and wrapping papers.